2D radiographs, cone‐beam computed tomography and 3D CBCT‐based planning software in access cavity preparation: A single blinded randomised controlled in vitro study. (24th September 2021) - Christofzik, David W.; Glandorf, Patrick; Conrad, Jonas; Fawzy El‐Sayed, Karim M.; Größner‐Schreiber, Birte; Dörfer, Christof E.
Abstract: This study compared endodontic access cavities prepared by operators of different experience levels (students, general‐practitioners and specialists), guided by periapical radiographs, cone‐beam computed tomography (CBCT) or 3D CBCT‐based planning software, with regards to tooth substance loss and preparation errors. Operators ( n = 34) prepared endodontic access cavities in 306 three‐dimensionally printed copies of human teeth with standardised anatomies. Access cavities were volumetrically assessed post‐operative using digital scans, while preparation errors were evaluated with CBCT. Tooth substance loss was significantly influenced by the operator's experience, being highest with students', followed by general‐practitioners and specialists ( P < 0.05), with no significant association with the employed imaging/planning modality. Pulp chamber floor, iatrogenic perforations and incomplete pulpal roof removal were insignificant between operator groups or imaging/planning modalities. It can be concluded that irrespective of advancement in imaging/planning modalities the practitioner's experience level remains to be the decisive factor significantly influencing tooth substance loss during endodontic access cavity preparations.